(untitled) (FIG Joint Land Administration Conference, 2025)
As a research gap, the lack of standardization in the construction of a database related to geotechnics, specifically to the data that support the maps of suitability for foundations, results in the impossibility of integrating these cartographic products. Furthermore, there is a considerable amount of data from the physical environment in the geological-geotechnical scope that need a correct computerization so that the knowledge generated about these preliminary data is constituted. Given this, this work aims to conceptually model geotechnical data, providing a path for structuring and making them available, in order to support the production of maps of suitability for foundations. Methodologically, the work used the OMT-G precepts to elaborate its conceptual model, establishing georeferenced and conventional classes, discriminating the necessary attributes contained in each one of them and putting them into a dictionary through the specifications of their characteristics and domains. Classes, relationship patterns and transformations were established in order to produce the results, that is, seven primary classes and eight class diagrams and transformations. When analyzing the results, it was possible to perceive that the geotechnical mapping could be analyzed from other perspectives, not only in the physical phases of data implementation, but mainly in the representations and characteristics that each one of them could have. The conceptual modeling performed was considered of universal application as it allows new documents and mappings to be integrated and adapted to established standards, regardless of software or hardware.